THE TRANSFER AND COMMERCIALISATION OF TECHNOLOGY FROM SOUTH AFRICA TO FOREIGN MARKETS IN THE FINANCIAL SERVICES INDUSTRY - Lubbe, FH; Brent, AC (The South African Journal of Industrial Engineering, 2009)
International technology transfer (ITT) processes are complex, risky, and often fail. When